Integrasi Sholat sebagai Terapi Emosional dalam Pendidikan dan Konseling Islam - Wasfiyah, Faza; Mutmainnah, Besse; Subhan, Nurul Izzah; Santalia, Indo; Yusriani, Yusriani (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study aims to explore perspectives on prayer (shalat) as a form of emotional therapy that can be integrated into Islamic education and counseling. Emotions are a crucial aspect of human life, influencing thought processes, behavior, and social relationships. When not properly managed, emotions can lead to psychological disorders such as anxiety and depression. In Islam, prayer is not merely a ritual act of worship but also serves as a spiritual tool that can help regulate emotions, calm the soul, and enhance mental well-being. Using a qualitative approach based on literature review, this paper outlines how the spiritual values embedded in prayer—such as mindfulness (khushu'), inner peace (tuma’ninah), and remembrance of God (dhikr)—have therapeutic effects on emotional stability. When performed regularly and with full awareness, prayer has been shown to reduce stress, strengthen self-control, and cultivate more peaceful and spiritually inclined individuals, both among students and counseling clients. The integration of prayer into the educational and counseling process in Islam offers a holistic approach that encompasses the intellectual, emotional, and spiritual dimensions of the individual in a unified and balanced way